Perceived Quality of Home Literacy Practice in Elementary School Students’: Parents’ Roles Toward Students’ Reading Literacy Achievement - Liana Mumrikoh; Djono; Nur Arifah Drajati (International Conference on Elementary Education, 2023)
The pandemic COVID-19 that began in 2019 has changed the learning system. During the pandemic, parental involvement contributes to students' academic performance, including reading literacy. Besides that, based on the research results from students’ tests in PISA 2018 and Puspendik reveals data that nationally homogeneous distribution of in students' reading literacy ability in Indonesia is 46.83 in the poor category. This research aims to examine relationship among parents’ education, family literacy practice, and students’ achievement of reading literacy in fifth grade. Data were collected through questionnaires and interviews. Participants involved were parents and teachers of fifth-grade students from nearby elementary schools in Surakarta. Data presentation (summary and code) and conclusions are used to analyze the data. Results of this study indicate that parental involvement is very important for the success of children's learning, especially reading literacy skills for pupils of elementary schools. They believe that directing, controlling, motivating, and reviewing children's assignments and influences on increasing their learning outcomes. It is expected to contribute the positive social change by providing useful information that can assist schools and teachers develop effective strategies to encourage parental involvement in home literacy and it has an impact on improving student academic outcomes at school.